DARI BUDAYA MENUJU BERPIKIR KRITIS MATEMATIKA: INTEGRASI ETNOMATEMATIKA PADA LEARNING TRAJECTORY GEOMETRI - Akbar, Ady; Fatimah; Asnita, Andi Ulmi; Andi Indra Sulestry; Atika Sahriyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to examine the effect of ethnomathematics learning based on a learning trajectory on elementary school students’ critical thinking skills in the topic of the volume of cubes and rectangular prisms. The study was motivated by students’ low critical thinking abilities and the limited ethnomathematics research explaining how cultural contexts can be systematically integrated into mathematics instruction. In this study, the learning process was designed based on an analysis of learning obstacles, which served as the foundation for developing a learning trajectory that connected local cultural contexts with formal mathematical concepts. The research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The participants consisted of 63 fifth-grade elementary school students, with 31 students in the experimental group and 32 students in the control group. Data were collected through a mathematical critical thinking test administered before and after the intervention. The data were analyzed using descriptive and inferential statistics. The results indicated that students in the experimental group achieved higher posttest and N-gain scores than those in the control group. Hypothesis testing also revealed a significant difference between the two groups. These findings demonstrate that ethnomathematics learning based on a learning trajectory is effective in improving students’ critical thinking skills. The study suggests that culture can serve as a meaningful learning resource when integrated through a didactic design that considers learning obstacles and students’ cognitive development.